A COMPARATIVE STUDY OF TAWKIL AL-WALI UNDER INDONESIAN AND MALAYSIAN LAW - Mohammad Hasan Bisyri; latifatun naila; Mohammad Ahsanul Khuluqi; Muhammad Jakfar Abdullah (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2025)
Taukil wali is when a marriage guardian gives their authority to someone else to perform a marriage. The goal of this study is to explain the differences and similarities in the legal rules about taukil wali. It also looks at how these rules have different legal effects in Indonesia and Malaysia. This is a type of legal research that uses existing laws and compares them. The information comes from documents like the Regulation of the Minister of Religious Affairs, the Compilation of Islamic Law, and Malaysian Islamic Family Law. The study found that both Indonesia and Malaysia have rules about taukil wali. They are similar in how they define taukil wali, who can be a guardian, what qualifications are needed for a deputy guardian, and why taukil wali is allowed. Indonesia has very clear and detailed rules for how this process works, which are in official laws. Malaysia uses general sharia principles and adjusts the process according to their own laws. When it comes to penalties, both countries have.